2021
DOI: 10.1007/s00068-021-01819-5
|View full text |Cite
|
Sign up to set email alerts
|

The significance of a concomitant clavicle fracture in flail chest patients: incidence, concomitant injuries, and outcome of 12,348 polytraumata from the TraumaRegister DGU®

Abstract: Purpose Isolated clavicle fractures (CF) rarely show complications, but their influence in the thorax trauma of the seriously injured still remains unclear. Some authors associate CF with a higher degree of chest injuries; therefore, the clavicle is meant to be a gatekeeper of the thorax. Methods A retrospective analysis of the TraumaRegister DGU® (project 2017-10) was carried out involving the years 2009–2016 (ISS ≥ 16, primary admission to a trauma cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…10 All patients underwent operative treatment for both injuries during the same session, which resulted in a mean ± SD HLOS of 18.8 ± 8.1 days. This is considerably higher compared with our study (median HLOS, 9 [5][6][7][8][9][10][11][12][13][14][15][16][17] days), which could be explained by differences in study population regarding the number of flail chests. However, their study would not be able to assess whether clavicula fixation would improve clinical outcome because of the small sample size and the noncomparative study design.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…10 All patients underwent operative treatment for both injuries during the same session, which resulted in a mean ± SD HLOS of 18.8 ± 8.1 days. This is considerably higher compared with our study (median HLOS, 9 [5][6][7][8][9][10][11][12][13][14][15][16][17] days), which could be explained by differences in study population regarding the number of flail chests. However, their study would not be able to assess whether clavicula fixation would improve clinical outcome because of the small sample size and the noncomparative study design.…”
Section: Discussioncontrasting
confidence: 83%
“…Therefore, patients with these combined injuries after blunt thorax trauma seem prone to (respiratory) complications and longer hospitalization. 10,11 There is an ongoing debate whether fixation of the clavicle fracture in patients with multiple concomitant rib fractures could be beneficial to provide additional stability to the chest wall and thereby improve clinical outcomes. 4 Despite the vast amount of literature describing rib fractures and clavicle fractures as individual entities, the mutual impact and subsequent management of these combined injuries remain unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 4 5) Several recent studies have reported that surgical stabilization of concomitant clavicle fractures in flail chest or multiple rib fractures offers good long-term benefits for return to the premorbid state. 6 7) Therefore, a shift towards operative treatment for displaced medial-end clavicle fractures has been suggested in recent research studies. 8 9) …”
mentioning
confidence: 99%
“…Various operative techniques including K-wire and tension band, fixation using plates (distal radial plate, small T-plate, standard T-locking plate, and pilon plate crossing the sternoclavicular [SC] joint), resection of the medial clavicle end, and arthrodesis of the SC joint have been described. 5 6 7 8 9 10 11) However, they show complications 8 9 10 11 12) including the limited movement of the shoulder girdle, loosening, migration, nonunion, neurovascular injury, 10 11) and displacement and breakage of plates and screws. 12) …”
mentioning
confidence: 99%